INVESTIGATING THE ROLE OF ANIMAL BEHAVIOUR IN THE TRANSMISSION AND SPREAD OF ZOONOTIC DISEASES - BATOOL , A; ARIF , R; SADDIQUE , H; KOMAL , M; FATIMA , U; ZAINAB , K; HABIB , MS; KHAN , A; CHAUDHRY , AA (Biological and Clinical Sciences Research Journal, 2023)
Emerging infectious diseases (EIDs) have significant public health and economic impacts and are frequently increasing. The study’s main objective is to investigate animal behavior’s role in the transmission and spread of zoonotic diseases. This analytical study was conducted at Ali Veterinary Hospital Lahore from August 2022 to January 2023. A crucial step in this study was the selection of study sites, which represented diverse ecological and geographical regions where zoonotic diseases were known to be prevalent. These sites were chosen to encompass a wide range of zoonotic disease types and to reflect areas where wildlife, domesticated animals, and humans frequently interacted. The selection process ensured a robust and representative dataset for analysis. A total of 12 study sites were selected across diverse geographical regions, encompassing ecosystems ranging from temperate forests to arid savannas. Behavioral data were collected from 5 species of animals, including raccoons, bats, and deer, known to be potential hosts or reservoirs for zoonotic diseases. Observations of animal behavior revealed several notable patterns. For instance, nocturnal animals such as bats exhibited communal roosting behavior in 80% of observations, while migratory birds displayed seasonal movement patterns covering an average distance of 500 miles. It is concluded that this study underscores the pivotal role of animal behavior in zoonotic disease transmission and highlights the need for a multidisciplinary approach to address this complex issue.